Aesthetics and Stress in TVET: Enhancing Student Well-Being and Creativity - Shen Wen; Faizal Amin Nur Yunus; Hashim, Suhaizal (Journal of Technical Education and Training, 2024)
It is imperative to provide adequate attention and motivation to contemporary Technical and Vocational Education and Training (TVET) graduates. This will enable them to cultivate a sense of self-confidence and explore avenues for career advancement through entrepreneurial endeavors, rather than relying primarily on traditional employment prospects within the labor market. Nevertheless, students in the TVET field encountered certain challenges, primarily stemming from the pressure to meet expectations and possess skills that exceeded their capacities. Stress is a psychological condition that individuals encounter as a result of the combined effects of mental and physical strain. The emotional well-being of an individual can be disrupted by environmental variables that provide a threat or disturbance. Integrating aesthetic education with stress management in TVET education can provide a holistic approach to teaching future students. Focusing on both the artistic aspects of gastronomic and stress management can help students handle challenges and improve their creativity. This study was conducted to ascertain the variables that influence the stress levels of TVET students at a vocational college in Johor, Malaysia. The study’s sample consisted of a total of 120 students. The questionnaires were employed as an instrument of gathering information pertaining to the surroundings and the individual’s personality traits. The data that was gathered underwent a descriptive analysis. The results of the study indicate that the various personality variables exhibited a significant value (M = 3.94) on the stress levels experienced by the students. Additionally, the stress levels resulting from environmental factors were also shown to be notably high (M = 4.05). The obtained correlation coefficient (r = 0.787) indicates a strong and favorable association between the environment and an individual’s personality. Nevertheless, the regression analysis findings indicate a lack of statistical significance (r = 0.00, r<0.05), hence demonstrating the absence of a meaningful correlation between environmental and individual personality variables. In conclusion, this study provides evidence to support the notion that both contextual and individual personality variables significantly contributed to the elevated levels of stress experienced by students in the TVET field. The majority of students concurred that their mental well-being and levels of stress will be influenced by both their surroundings and individual dispositions.